2016
DOI: 10.1016/j.gene.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function and regulation of jade family PHD finger 1 (JADE1)

Abstract: The family of JADE proteins includes three paralogues encoded by individual genes and designated PHF17 (JADE1), PHF16 (JADE2), and PHF15 (JADE3). All three JADE proteins bear in tandem two Plant Homeo-domains (PHD) which are zinc finger domains. This review focuses on one member of the JADE family, JADE1. Studies addressing the biochemical, cellular and biological role of JADE1 are discussed. Recent discoveries of JADE1 function in the regulation of the epithelial cell cycle with potential relevance to disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…PHF17), a transcription factor, contains two variants: JADE1-L (a long form with 842 amino acids) and JADE1-S (a short form without a C-terminal fragment of 333 amino acids) (Borgal et al, 2014 ; Siriwardana et al, 2015 ). Although the role of JADE1 remains elusive, the protein exhibits histone acetyltransferase (HAT) activity and acts as a co-factor of the HBO1 complex in histone H4 acetylation during gene regulation, which plays crucial roles in cell cycle regulation (Panchenko et al, 2004 ; Foy et al, 2008 ; Panchenko, 2016 ; Han et al, 2018 ). The suppression of JADE1 (both JADE1-L and JADE1-S) by siRNA knockdown results in suppression of DNA synthesis in cultured epithelial cell lines and primary fibroblasts (Havasi et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…PHF17), a transcription factor, contains two variants: JADE1-L (a long form with 842 amino acids) and JADE1-S (a short form without a C-terminal fragment of 333 amino acids) (Borgal et al, 2014 ; Siriwardana et al, 2015 ). Although the role of JADE1 remains elusive, the protein exhibits histone acetyltransferase (HAT) activity and acts as a co-factor of the HBO1 complex in histone H4 acetylation during gene regulation, which plays crucial roles in cell cycle regulation (Panchenko et al, 2004 ; Foy et al, 2008 ; Panchenko, 2016 ; Han et al, 2018 ). The suppression of JADE1 (both JADE1-L and JADE1-S) by siRNA knockdown results in suppression of DNA synthesis in cultured epithelial cell lines and primary fibroblasts (Havasi et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“… Xu et al (2019) showed that miR-6840-3p bound to ZEB2-AS1 and then targeted PLXNB1 to promote the progression of laryngeal squamous cell carcinoma. JADE2 (gene for apoptosis and differentiation in epithelia 2) is a member of the small JADE family ( Panchenko, 2016 ). Several studies found that JADE2 was associated with histone modification in ovarian cancer and acquired immune deficiency syndrome ( Quintela et al, 2019 ; Maxwell et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Phf16 is a member of a family of large proteins containing plant homeo domain (PHD)-type zinc fingers. 33 However, functions of Pnpla3 and Phf16 in adipocyte differentiation remain unclear. Therefore, further analyses may provide insights into the roles of Pnpla3 and Phf16 genes in adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%